Combating Excessive Food Consumption Through Augmented Reality Packaging: An Explorative Study of Generation Z - Asriadi Masnar; Firdania Octaviany Hidayah; Isma Ar Rachmah; Nurbaya Nurbaya (Politeknik Kesehatan Kemenkes Mamuju, 2023)
In 2020, The Indonesian Food and Drug Authority published Front of Pack Nutrition Labelling to ease consumers decide their diet preferences. In line with this effort, digital campaigns can effectively educate society and reduce the high consumption of Sugar, Salt, and Fat (SSF) in Indonesia. This research discusses the effectiveness of SSF consumption restriction messages delivered using Augmented Reality (AR) technology. This research uses a quantitative descriptive method. The data were collected from randomly selected 100 youngsters living in Jakarta, Bogor, Depok, Tangerang dan Bekasi (Jabodetabek) area and followed by the EPIC (Empathy, Persuasion, Impact, and Communication) model analysis. All four dimensions of EPIC fell on effective category within range 4.23-4.29 out of 5.8. These findings suggest that, in general, the advertisement for limiting the consumption of SSF with Augmented Reality media stands in the very effective category with a final score of 4.25 and represent that AR application in packaging can effectively be used for promoting or advertisising particular information.